Aplicação da teoria do funcional da densidade (DFT) e da teoria quântica de átomos em moléculas (QTAIM) no entendimento da oxidação anódica de poluentes promovida pelo ânodo de diamante dopado com boro (BDD) - Silva, Ámison Rick Lopes da (2020)
In environmental electrochemistry there is a focus on effluent decontamination using catalytic techniques and materials that promote the oxidation / mineralization of organic matter present in the effluent. The electrochemistry applied in this context is a treatment that fits in green chemistry, as it avoids the use of environmentally aggressive reagents. The chemical complexity surrounding the oxidation of pollutant molecules is studied in the literature step by step in order to understand and improve processes at the molecular level. In order to better understand at molecular level these reaction processes, computational studies applied with collaborations from the areas of environmental electrochemistry and theoretical chemistry to contribute to the literature. Using the results of the electroanalytical techniques: cyclic voltammetry (CV) and differentiated pulse voltammetry (DPV) were applied to the system with caffeine, H2SO4 support electrolyte and boron-doped diamond anode (BDD). The electroanalytical profile presented for this system resulted in an oxidative peak that characterizes caffeine oxidation as a direct oxidation, in other words, a peak that occurs before water discharge potential, indicating that caffeine oxidation occurs directly on the surface of the BDD. From the information provided by the experimental measurements of CV and PDV, a BDD surface cluster was computationally constructed to verify caffeine-electrode interactions, obtaining energy parameters and interaction points by Density Functional Theory (DFT) calculations, Quantum Theory of Atoms in Molecules (QTAIM) and Electronic Localization Function (ELF). According to the energy analysis results obtained from the DFT, the most and least stable geometries were determined by interaction energy (IE). Topological data of interaction geometries were obtained using QTAIM and ELF to verify the influences that occurred during the interaction and to correlate with IE. In another system that treats anodic oxidation as a more active scenario using BDD to mineralize pollutant, Eriochrome Black T (EBT) in solution in the presence of Mg2+ and Ca2+ cations. Batch electrooxidation and monitoring the decontamination by Chemical Oxygen Demand (COD) and Visible Ultraviolet Spectroscopy (UV-VIS), the behavior observed was the opposite of what was reported in the literature when the treatment used was electro-fenton. In this scenario, use of DFT to obtain the structures of the complexes formed between EBT and cations, and then QTAIM calculations applied to the complexes, in order to analyze the metal-ligand bonds in the structure of the adult complexes formed. The electron density in these bonds reveals the strength of the complexes, so that it was possible to compare the order of ease in undergoing electro-oxidation among the complexes formed, this order of ease took into account complexes with tri and hexavalent coordination sphere, for both. The coordinating sphere complexes did not change the results.